Science-policy-public interface toward ocean sustainability: An empirical study using legal documents, scientific publications, and public inquiry logs in Japan - Sugimoto, Aoi; Tajima, Hidetomo; Sugaya, Takuma; Watari, Shingo (Frontiers in Marine Science, 2023)
Many countries have governmental fisheries science organizations, each of which should play a critical role in achieving ocean sustainability by leading the fisheries science in each country’s specific contexts and beyond. In the context of the UN Decade of Ocean Science (UNDOS), understanding the interface of science, policy, and public interest around fisheries is increasingly recognized as critically important for realizing effective knowledge exchange and co-creating desired futures. This study aims to illuminate the interface of the above three facets as a guide to have better outcomes in the UNDOS timeframe. We used a case study of Japan – a country with extensive seafood production and consumption, and analyzed 1) the scientific performance of the Japan Fisheries Research and Education Agency (JFRA), a national fisheries research organization in the country through peer-reviewed papers published by JFRA researchers from 2004–2018, 2) policy needs through annual white papers published by Fisheries Agency from 1989–2018, and 3) public interest around fisheries through public inquiry logs accumulated at JFRA from 2004–2018. The results indicated the following: 1) JFRA was originally a part of fisheries policies, and both science and policy were inherently based on the fisheries practices in the “real world” in Japan. However, over the last fifteen years, the scientific performance has heavily focused on bio-physical dimensions of fisheries such areas as “Stock assessment,” “Fisheries Oceanography,” and “Stock enhancement.” 2) Japanese fisheries policy priority has shifted from relatively simple, straightforward keywords focusing on primary fisheries production (from 1989 to 1998) to more complex, multidimensional fisheries systems, including marine resources, producers, processors, and consumers in/outside of the country (from 2009–2018) over the last three decades. 3) Public fisheries/ocean literacy seems limited, despite the rich history of seafood consumption, cultural bond with fisheries, and inherent close relationship among fisheries science, policy, and resource users. Based on the results, we discuss that JFRA sciences, fisheries policy, and the public are contemporary pursuing different interests. To overcome this situation, one important area that JFRA (and any other marine/fisheries research organizations) needs is to reconnect science and public interest through strengthening human dimension works and science communication. For the public side, literacy development among wider stakeholders is one of the most emergent works to be addressed. This is one of the first case studies of science-policy-public interface through empirical data, particularly with the public inquiry log, and the “non-Western” country case study on this topic. This will encourage other empirical studies from countries with various social/cultural/political backgrounds to enrich the perspective of fisheries science-policy-public interface studies globally.